A Review of the Resilience of Rural Communities in the Face of Climate Change - Yohanes Kamakaula; Komang Ariyanto; Roys Qaribilla; Aghus Jamaludin Kharis; Farikhul Muafiq; Ratnawati Yuni Suryandari (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study was to examine the multifaceted nature of rural community resilience in the face of climate change. It sought to identify how social, ecological, and institutional factors interact to support or hinder adaptive capacity in rural settings, particularly where infrastructure is limited. Materials and methods. This review drew upon global literature and case studies to explore resilience frameworks and adaptation strategies. The analysis integrated structural approaches, including the Baseline Resilience Indicators for Communities (BRIC) and the STAR model (Specific assets, Tradeable specialization, Access to markets, Resources), to provide lenses for assessing rural resilience and informing policy interventions. Results. The review revealed that social capital, traditional ecological knowledge, and livelihood diversity are critical foundations for resilience and transformative potential. Adaptation strategies such as diversified agriculture, agroforestry, participatory planning, and ecosystem-based approaches were found to be effective in enhancing socio-ecological sustainability. However, challenges such as limited infrastructure, insufficient institutional support, unequal access to finance and technology, and erosion of local knowledge persist and constrain resilience-building efforts. Conclusions. This study concludes that while promising practices exist, gaps remain in comprehensive frameworks and in the design of inclusive, participatory policies. Strengthening rural resilience requires localized, equity-driven approaches that integrate local knowledge with institutional support, while addressing systemic barriers to resources and infrastructure. Future research should prioritize community-driven models and multi-scalar strategies to better fortify rural resilience amid accelerating global environmental change.